MOTION GRAPHIC VIDEO DESIGN FOR THE WORK PROGRAM OF DPR-RI MEMBERS - Deli Deli; Celine Te (ConCEPt - Conference on Community Engagement Project, 2022)
Cen Sui Lan is a member of the House of Representatives of the Republic of Indonesia in the Riau Islands constituency in her 2019-2021 term of office. During her tenure, there have been many programs carried out, such as socialization of the four pillars, distributions of daily necessities, and the construction of STT flats. Even so, she faced a dire problem. Her works have not been widely known by the citizens of Batam. Therefore, Cen Sui Lan needed a form of media, such as motion graphics, to inform the Batam community of the programs she had done so far. The methodology applied in this research is an applied method by developing motion graphics videos using VideoScribe software and Adobe Premiere Pro. The results of the motion graphics videos will be uploaded to Cen Sui Lan's social media. The video will give more information about the works of Cen Sui Lan as a member of the House of Representatives and improve the public image for Cen Sui Lan's performance.